2009
DOI: 10.1002/pssa.200881615
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in tomographic small‐angle X‐ray scattering

Abstract: Small‐angle X‐ray scattering (SAXS) has become a standard tool for the investigation of nano‐structured materials with applications in many fields of science. Scanning tomography adds three‐dimensional information to the method. We investigate the validity of the tomographic model in SAXS tomography. We identify the requirement of local rotational invariance of the SAXS cross section and discuss the role of coherence in the framework of SAXS tomography. A tomography experiment performed on nanoporous glass is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…To measure three-dimensional samples without sectioning, scanning SAXS has to be combined with computed tomography (CT) techniques. If the scattering is invariant with respect to sample rotation (Feldkamp et al, 2009), measurements taken at different angles for one rotation axis are enough and a standard reconstruction algorithm, such as filtered back-projection or simultaneous algebraic reconstruction technique (SART), can be used. Rotational invariance applies for isotropically scattering samples, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure three-dimensional samples without sectioning, scanning SAXS has to be combined with computed tomography (CT) techniques. If the scattering is invariant with respect to sample rotation (Feldkamp et al, 2009), measurements taken at different angles for one rotation axis are enough and a standard reconstruction algorithm, such as filtered back-projection or simultaneous algebraic reconstruction technique (SART), can be used. Rotational invariance applies for isotropically scattering samples, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Rotational invariance applies for isotropically scattering samples, i.e. with no preferred orientation of the nanostructure or for unidirectional orientation of the nanostructure parallel to the rotation axis (Schroer et al, 2006;Feldkamp et al, 2009;Jensen et al, 2011). Skjønsfjell et al (2016) have shown that, with strict assumptions on the sample, the orientation distribution can be retrieved from measurements using a single rotation axis by fitting a model of the X-ray scattering to the experimental SAXS pattern.…”
Section: Introductionmentioning
confidence: 99%
“…This model can work with popular acquisition modes for x-ray small-angle scattering signal, such as pencil beam imaging [7,8], fan beam scanning [9,10], and x-ray Talbot-Lau interferometry [11]. Our numerical simulation and phantom experiments have shown that the proposed darkfield tomographic imaging method can reconstruct highquality small-angle scattering images with superior contrast resolution relative to its conventional attenuation-based CT counterpart.…”
Section: Resultsmentioning
confidence: 91%
“…1(a-b). We also performed a comparison with the conventional model of dark-field tomographic imaging, which states that the measured small-angle scattering patterns normalized by the transmitted intensity is a line integral of smallangle scattering coefficient [7][8][9][10], that is,…”
Section: Numerical and Phantom Experiments A Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation